What drives the relationship between inflation and price dispersion? Market power vs. price rigidity - Sascha Becker (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2011)
Recent monetary search and Calvo-type models predict that the relationship between inflation and price dispersion is U-shaped, implying an optimal rate of inflation above zero. Moreover, monetary search models emphasize a critical dependence of the real effects of inflation on sellers' market power, whereas Calvotype models suggest that the degree of price rigidity significantly affects the inflation - price dispersion nexus. Using a new set of highly disaggregated sectoral price data from a panel of European countries, this paper contributes to the literature by testing the empirical relevance of these two theoretical predictions. In line with monetary search theory, a U-shaped profile is found, provided that markups are sufficiently high, but the relationship breaks down under a more competitive environment. Contrarily, no evidence is found to support the contentions of Calvo-type models: U-shaped effects of inflation occur in product sectors with sticky as well as highly flexible prices.
Keywords: C23; D40; E31; F15; 330; inflation; relative price variability; price level index; Euro-area; market structure; monetary search model; dynamic panel data models; Taxigewerbe; Betrug; Vertrauensgüter; Asymmetrische Information; Feldforschung; Athen